Degree centrality and functional connections in presbycusis with and without cognitive impairments - Xu, Xiao-Min; Liu, Yin; Feng, Yuan; Xu, Jin-Jing; Gao, Jun; Salvi, Richard; Wu, Yuanqing; Yin, Xindao; Chen, Yu-Chen (Brain imaging and behavior, 2022)
Presbycusis is a major public issue that affecting elderly adults. However, the neural substrates between normal cognition and cognitive deficits in these patients need to be illustrated. 47 patients with presbycusis and 33 well-matched healthy controls were recruited in present study. Each subject underwent pure-tone audiometry (PTA), MRI scanning and cognition evaluations, then we found 22 patients with cognitive deficits and 25 patients with common cognition. We analyzed the Degree centrality (DC) characteristics among three groups, and try to recognize key nodes which contribute significantly. Subsequent functional connectivity analysis was applied using the key nodes as seeds. Compared with controls, presbycusis without cognitive impairments showed deceased DC in superior temporal gyrus (STG), inferior frontal gyrus (IFG) and supramarginal gyrus (SMG). Additionally, presbycusis with cognitive impairments showed enhanced DC in fusiform gurus (FFG), cerebellum and para-hippocampal gyrus (PHG), while weakened DC in SMG, middle frontal gyrus (IFG) and inferior Parietal lobule (IPL). Compared with normal cognition, increased DC value of cerebellum and STG, as well as decreased DC value of IPL in presbycusis with cognitive impairments were observed. We noticed that SMG may play an important role. Then the left and right SMG were used as seeds in functional connections analysis. With the seed set at left SMG, presbycusis without cognitive impairments showed decreases connections with cerebellum, temporal pole (TP), superior temporal gyrus (STG) and median cingulate cortex (MCC). Presbycusis with cognitive impairments showed weakened connectivity with cerebellum, IFG, IPL and superior frontal gyrus (SFG). The right SMG showed decrease connections with cerebellum, middle temporal gyrus (MTG), STG and increase connection with middle frontal gyrus (MFG) in presbycusis without cognitive impairments. While the right SMG showed enhanced connections with left TP, caudate, anterior cingulate cortex (ACC), angular, SFG and weakened connectivity with right SFG presbycusis with cognitive impairments. In comparison with normal cognition and impaired cognition, MFG, IFG, PHG, rolandic operculum and cerebellum were involved. These findings enriched our understanding of the neural mechanisms underlying cognitive impairments associated with presbycusis and may serve as a potential imaging biomarker for investigating and predicting cognitive difficulties.